PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA MCDONALD’S EMERALD BINTARO TANGERANG SELATAN - Argi Ardiansyah (Jurnal Menara, 2024)
This research aims to determine the effect of training and work discipline on employee performance, both partially and simultaneously at McDonald's Emerald Bintaro, South Tangerang. The method used in this research is quantitative. The analysis technique uses statistical analysis by testing validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple linear regression tests, correlation coefficient tests, coefficient of determination tests, t tests and F tests. The population is employees of Mcdonald's Emerald Bintaro, South Tangerang. With a saturated sample, 85 or the entire population is used. The results of this research based on the coefficient of determination show that training and work discipline have a contribution to employee performance of 74.3%. The results of the research show that the correlation coefficient value of training on employee performance is 0.749, meaning that the two variables have a strong level of relationship, the correlation coefficient value of work discipline on performance employees is 0.860, meaning that the two variables have a very strong level of relationship. The results of testing the simultaneous influence of the independent variable on the dependent variable obtained a value of Fcount = 118.622 > Ftable value = 3.11, so the hypothesis was accepted. So it can be concluded that there is a significant influence between training and work discipline on employee performance at McDonald's Emerald Bintaro, South Tangerang